Three‐month primary efficacy data for the SUCCESS Trial; a phase III, multi‐center, prospective, randomized, controlled study treating female stress urinary incontinence with the vesair intravesical balloon. Issue 1 (2nd November 2017) - McCammon, Kurt; Jacoby, Karny; Kalota, Susan; Snyder, Jeffrey; Cline, Kevin; Robertson, Kaiser; Rardin, Charles; Kahan, Randall; Green, Lonny; Zuckerman, Jack; Rovner, Eric
Abstract : Aims: The SUCCESS trial is a phase III study of the Vesair® balloon in the United States for female stress urinary incontinence (SUI). The purpose of this manuscript is to present the 3 month primary efficacy and tolerability outcome data. Methods: The SUCCESS trial is a multi‐center, prospective, single blind, randomized, sham‐controlled study. Subjects were randomized on a 2.33:1 basis to either Vesair balloon placement or placebo. The primary efficacy endpoint was a composite of both a >50% reduction from baseline on 1 h provocative pad weight test and a ≥10‐point improvement in symptoms on the Incontinence Quality of Life Survey (I‐QOL) questionnaire assessed at the 3 month study visit. Results: A total of 221 subjects were randomized, including 157 treatment arm subjects and 64 controls. The 3 month composite primary efficacy endpoint was achieved in 42.1% of treatment group subjects compared with 28.1% of controls on intention‐to‐treat analysis ( p = 0.046). Treatment arm subjects were significantly more likely to report at least a 50% reduction in incontinence frequency on 7‐day voiding diary (55.2% vs 32.3%, P = 0.002, ITT) and more commonly reported their incontinence was improved on Patient Global Impression of Improvement in Incontinence (PGI‐I) at 3 months compared with controls (58.0% vs 37.7%, P = 0.007, ITT). No device‐ or procedure‐related serious adverse events nor unanticipated adverse events were reported and no cases of urinary retention were observed. All adverse events fully resolved following balloon removal. Conclusions: In this phase three trial, the Vesair intravesical balloon achieved 3 month primary and secondary endpoints both objectively and subjectively.